Effect of the Extraction Solvent Polarity and the Ratio of Feed and Solvent on the Phytochemical Content and Antioxidant Activity of Red Betel Leaves (Piper crocatum) - Monika Rahardjo; Gelora Mangalik; Monang Sihombing; Junet Franzisca da Costa (Talenta Publisher, 2018)
Red betel leaf (Piper crocatum) is a plant growing in tropical areas and previously known as an ornamental plant, but then later used as medicinal plant. Previous researches found that red betel leaves contain bioactive compounds such as alkaloids, flavonoids, tannins, and many more that have potential to be used as antioxidant. The extractions were carried out using variations of solvent types (ethanol, water, and ethyl acetate) and feed to solvent (F:S) ratios in g/ml (F:S=1:20, F:S=1:25, F:S=1:30). The best conditions from this research were the usage of ethanol as the solvent. In addition to its ability to extract the compounds potential as antioxidant and F:S ratio of 1:30, it could give highest yield of extract. Variation of solvent type and variation of F:S have significant effect on the value of antioxidant activity (IC50) of the red betel leaf sample.